Confiabilidad Y Validez Del Cuestionario De Habilidades Psicológicas Para Árbitros De Fútbol (CHP) Escalafonados Del Eje Cafetero (2015)
The aim of this study was to analyze the psychometric properties of reliability and validity of a questionnaire of psychological skills applied to a sample (n = 54) referees escalafonados distributed in the three categories of Colombian professional soccer, which are category C, Professional category Professional category 1A and 1B, these referees associations belonging to the following departments, Quindio, Risaralda and Caldas. The method used is an experimental investigation of cross section, a description link. For the study Psychological Skills Questionnaire for football referees (PSQ). The reliability of the questionnaire was verified by analyzing the internal consistency, for which the Cronbach's alpha coefficient was used. The result showed, except communication and team cohesion than 0.3 values (between 0.49 and 0.34) throwing a reliability index of the questionnaire (0.49) .the validity for Exploratory Factor Analysis (EFA) was decided to be impossible to determine the validity of construct, for this reason I took an expert judgment while concluding that the questionnaire is not interpreted as an exact reality and must be deepened through observations and interviews